Analisis Laporan Keuangan untuk Pengukuran Kinerja pada PT Pioneer - Hastoni, Hastoni; Wijaya, Tjandra (Jurnal Ilmiah Ranggagading (JIR), 2007)
The purpose of this research is to find out the capability and performance of a firm in analizing finance accounting and to know if the firm has given sufficient information in accordance with the will of decision makers. The research was done at Center Jakarta-based PT Pioneer which produce diesel machine. The result of this research shows that PT Pioneer has good performance. The capability of the firm in achieving good performance can be accounted for by the firm. The performance can be measured by doing analysis of finance accounting that encompass liquidity analysis, activity analysis, and profitability analysis. Profitability analysis was studied better than liquidity analysis and activity analysis. Keywords: Finance accounting analysis; Performance